Handicaps Associated with Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The prevalence and severity of handicaps in 217 children and adolescents with epilepsy were assessed at the University of Goteborg, Ostra Hospital, Sweden, using the World Health Organization International Classification of Impairments, Disabilities and Handicaps (ICIDH).